The Shingle Sawing Machine in British Columbia 1901 to 1925 - Griffin, Robert (Material Culture Review, 1981)
The production and use of shingle machinery formed a significant aspect of British Columbia's early industrial development. The early shingle machines, designed and manufactured in the East, were drastically redesigned in British Columbia and then produced by local firms. The production of these new machines provided several British Columbia engineering firms, especially the Schaake Machine Works and Let-son and Burpee Limited, with a significant part of their revenue and thus with an opportunity for expansion and the development of additional products. A great deal of effort on the part of British Columbia's mechanics and engineers went into the continual redesign of the shingle sawing machine, probably as a result of increasing competition. Production of the new shingle machines gradually spread throughout the Pacific Northwest and then into the eastern United States. Frequently the technical change was not just the reworking of previously applied principles but rather involved the application of entirely new principles, new at least to shingle machinery. The introduction of these machines occurred at a time when the British Columbia shingle industry entered a period oftremendous growth. Due to the much higher quality of shingles produced by the new machines, the province's shingle manufacturers were able to penetrate and maintain a share of major markets in the eastern United States. Résumé La production et l'utilisation de machines à fabriquer les bardeaux marquèrent les débuts de l'industrialisation en Colombie-Britannique. Les entreprises de cette province modifièrent radicalement le dessin des premières machines à bardeaux fabriqués dans l'Est avant d'en commencer la production. Plusieurs bureaux d'ingénieurs de Colombie-Britannique, en particulier les sociétés Schaake Machine Works et Letson and Burpee Limited, tiraient une importante part de leurs revenus de la fabrication de ces nouvelles machines et purent ainsi s'agrandir et mettre au point de nouveaux produits. Les techniciens et les ingénieurs, probablement sous la pression de la concurrence croissante, consacrèrent leurs efforts au perfectionnement continuel de la scie à bardeaux. La fabrication des nouvelles machines s'étendit peu à peu à la côte du Pacifique, puis à l'Est des Etats-Unis. L'amélioration technique était souvent plus qu'un simple remaniement de principes déjà appliqués et faisait plutôt intervenir des principes innovateurs, encore jamais appliqués à la fabrication du bardeau. Les machines firent leur apparition au moment où l'industrie du bardeau de la Colombie-Britrannique entrait dans une période de croissance accélérée. Grâce à la qualité très supérieure de leurs produits, les fabricants de la province firent une percée sur les grands marchés de l'Est des États- Unis et surent s'y maintenir.